2021
DOI: 10.1007/s12598-020-01649-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and perspective in metal coordination materials-based electrode materials for potassium-ion batteries

Abstract: Recently, to ameliorate the forthcoming energy crisis, sustainable energy conversion and storage devices have been extensively investigated. Potassium-ion batteries (KIBs) have aroused widespread attention in these very active research applications due to their earth abundance and similar low redox potential compared to Li-ion batteries (LIBs). It is critical to develop electrode materials with large ion diffusion channels and robust structures for long cycling performance in KIBs. Metal coordination materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 101 publications
0
27
0
1
Order By: Relevance
“…They have been the focus of considerable research that demonstrated their promising energy and power performance at room temperature. [15][16][17][18][19] The synthesis of PB is often a relatively easy and scalable onepot process that mainly proceeds hydrothermally, by precipitation, or by electrodeposition. 13,[20][21][22][23] Among the three methods, precipitation is the most scalable and energy efficient, as it normally proceeds rapidly upon adding the metal ion salt to a solution of the cyanide ion salt precursor.…”
Section: Introductionmentioning
confidence: 99%
“…They have been the focus of considerable research that demonstrated their promising energy and power performance at room temperature. [15][16][17][18][19] The synthesis of PB is often a relatively easy and scalable onepot process that mainly proceeds hydrothermally, by precipitation, or by electrodeposition. 13,[20][21][22][23] Among the three methods, precipitation is the most scalable and energy efficient, as it normally proceeds rapidly upon adding the metal ion salt to a solution of the cyanide ion salt precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the distribution of lithium on earth is uneven, and its reserves are limited. In addition, there are still some problems that need to be solved for LIBs, such as poor low-temperature performance, safety problems, and high cost ( Liu G. et al, 2018 ; Xing et al, 2020 ; Sui D. et al, 2021 ; Wang et al, 2021c ; Shi et al, 2021 ). As a potential substitute for LIBs in energy storage devices, SIBs have attracted extensive attention because sodium is much cheaper than lithium, environmentally friendly, and SIBs show the same energy storage mechanism as LIBs ( Wang et al, 2018 ; Cao et al, 2020 ; Sui et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly effective utilization of all these energy sources is seriously hindered by their intermittent production and uneven geographical distribution [ 7 ]. High-performance energy storage materials and devices with characteristics of high energy and power densities, low cost and long-term stability have become a worldwide research hot topic for both academia and industry [ 8 , 9 , 10 , 11 , 12 ]. In addition, the rapid development of consumer electronics and electric vehicles also calls for high-performance energy storage devices [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%